2022
DOI: 10.3390/jpm12061015
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Investigation of Mandibular Lingula: A Literature Review

Abstract: Purpose: The purpose of the study was to review the literature on the shape of the mandibular lingula. Methods: English articles published from 1970 to 2021 in databases (PubMed, Web of Science, and Embase) were selected. Articles meeting the search strategy were evaluated based on the eligibility criteria (participants aged 18 years and over). Dry mandibles and cone beam computed tomography (CBCT) images were used as research materials. The shapes of mandibular lingula were classified as triangular, truncated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A previous study performed by Tuli et al [4] reported four shape variations of the ML; 68.5% of triangular shaped ML, 15.8% of truncated shape, 10.9% of nodular, and 4.8% of assimilated shape. Somewhat similarly, Hsu et al [56] observed variation of shape predominance based on the method of study, namely dry mandible and CBCT; in the dry mandibular study, the predominant shape of the ML was found to be 39% triangular, while in CBCT the most frequent shape found was nodular in 50.6% of studied cases. Both studies, however, concluded that the least common shape variation of the ML was the assimilated type.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A previous study performed by Tuli et al [4] reported four shape variations of the ML; 68.5% of triangular shaped ML, 15.8% of truncated shape, 10.9% of nodular, and 4.8% of assimilated shape. Somewhat similarly, Hsu et al [56] observed variation of shape predominance based on the method of study, namely dry mandible and CBCT; in the dry mandibular study, the predominant shape of the ML was found to be 39% triangular, while in CBCT the most frequent shape found was nodular in 50.6% of studied cases. Both studies, however, concluded that the least common shape variation of the ML was the assimilated type.…”
Section: Discussionmentioning
confidence: 71%
“…The second most common bilateral shape was found to be truncated, with a prevalence rate of 68.58%, followed by nodular (64.79%) and assimilated (62.11%). Hsu et al [56] also reported a predominance of bilateral symmetry among both the investigated dry mandible and CBCT study groups. With respect to gender-determining factors, Alves and Deana [7] claimed that the truncated type was found more commonly in women, while triangular was found more commonly in men.…”
Section: Discussionmentioning
confidence: 86%
“…[10][11][12][13][14]17,18 The findings in this field have been controversial due to variations in the evaluation techniques employed and the need for consistent reference planes defined in these studies. 2,4,13,17,[19][20][21][22][23][24][25] These controversies include not only the absolute values of the measurements regarding the ML reference point, but also the correlation between factors such as gender, angle classification and growth pattern on the ML position.…”
Section: Introductionmentioning
confidence: 99%